ANALISIS DISTRACTOR DALAM SOAL PILIHAN GANDA UJIAN SEMESTER MATA PELAJARAN SEJARAH PADA SISWA KELAS XI IPS SMAN 8 MANDAU - Nadila Putri Ningsih; Bedriati Ibrahim; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: SMA Negeri 8 Mandau is one of the largest schools in Mandau sub-district, was established in the 2011/2012 school year and is A accredited according to SK: 404/BAP-SM/KP-09/X/2015. This thesis aims to determine the analysis of the distractor function in the multiple choice odd semester exam in class XI students of SMA N 8 Mandau. This type of research is descriptive. The data sources of this study are multiple choice questions and answer sheets from a total of 196 students to be analyzed quantitatively. Quantitative analysis requires a formula that is used to determine the distractor function of the number of students choosing each option from the distractors. No less than 6 students with good criteria, choice A was chosen by 3 with bad criteria and C was selected no less than 2 students with bad criteria. Other choices in all questions also have good and very good criteria, but some choices also need to be corrected because they have bad criteria, and interchanged because they have bad and very bad criteria.Key Words: Distractor analysis, Multiple Choice Questions, History, SMA Negeri 8 Mandau